Spectrophotometric Method for the Determination of Nebivolol Hydrochloride in Bulk and Pharmaceutical Formulations - A. Lakshmana Rao; K. R. Rajeswari; G. G. Sankar (E-Journal of Chemistry)
A simple, sensitive, highly accurate spectrophotometric method in UV region has been developed for the determination of nebivolol hydrochloride in bulk and pharmaceutical formulations. Nebivolol hydrochloride is an antihypertensive drug, which shows maximum absorbance at 281 nm with apparent molar absorptivity of 5.37208 × 103 mol-1 cm-1. Beer’s law was obeyed in the concentration range of 4-60 μg/mL. The slope, intercept and correlation coefficient were also calculated. The proposed method has been successfully used for the analysis of the drug in pure and its tablet dosage forms. Results of percentage recovery shows that the method was not affected by the presence of common excipients. The percentage assay of nebivolol hydrochloride was 98.75 and 99.02 respectively. The method was validated by sensitivity and precision which proves suitability of proposed method for the routine estimation of nebivolol in bulk and pharmaceutical formulations.